Optimising Organisational Performance Through Human Resource Management Strategy and Technology Integration to Enhance Innovation - Tusriyanto; Sulaeman, Moh. Muklis; Nurcholidah, Lilik (Technology and Society Perspectives (TACIT), 2023)
In the evolving era of digitalization and globalization, organizations face increasingly complex and dynamic challenges. Rapidly advancing information technology and intense global market competition necessitate organizations to evaluate and enhance their performance to remain relevant and competitive. This research aims to investi-gate best practices in HRM and technology integration to promote innovation, with a focus on its positive impact on organizational performance. The approach entails conducting an in-depth examination of literature through qualitative analysis, aiming to attain a comprehensive comprehension of the topic spanning the years 2001 to 2023. The study's findings indicate that human resource management (HRM) strategies focusing on employee recruitment, training, and development, along with effective performance management, form the basis for a competent team. A positive work environment with constructive feedback enhances productivity. Technology integration, through information and communication technology (ICT) and technology based HRM systems, improves operational efficiency. The use of technology for decision-making, administration, and employee data analysis accelerates business processes. Technology integration also stimulates innovation through collaboration and artificial intelligence, aiding organizations in identifying new opportunities in the digital era.